MODEL STUDENT CENTERED LEARNING (SCL) DI SEKOLAH DASAR (SD) YANG INOVATIF TERINTEGRASI PEMBELAJARAN TERPADU - Uslan Uslan; Nuriyah Nuriyah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
Learning model as a conceptual framework used as a guide in learning. An example of a commonly used learning model is student centered learning (SCL). Thus, the adoption of an innovative SCL model helps learners understand concepts by connecting between the content learned and the real life of learners that are integrated into The objective of this research is to integrate integrated learning for students in elementary school (SD) into innovative SCL model.This type of research is literature research with documentation study method from various sources of books and scientific journals Discussion of research, reviewing: innovative integrated learning models in SD, SCL model function in KBM, integrated learning benefits, and SCL model correlation with integrated learning.Keywords: SCL SD Model, Innovative, Integrated Learning